Research on Social Factors Encouraging Girls' Participation in Sports - Theocharous, Antonis L.; Panagopoulou, Maria; Giannoulis, Petros; Kosma, Panagiotis (My University, 2019)
This project, its results, outcomes and potential are dedicated to the memory of our wonderful colleague, Sture Hermansson, who passed away in 2018. Sture was an inspirational figure, who thrived on learning and helping others learn. Sture’s most special gift to the profession was his light-hearted and joyful approach to life and work.
Keywords: Encouraging Girls; Sport